Antibióticos utilizados em dieta artificial para criação de Diatraea saccharalis visando o controle de protozoários - Lemes, Marilia de Aquino e Saglietti (Universidade Federal de São Carlos, 2022)
The biological control of the sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) by the parasitoid Cotesia flavipes (Hymenoptera: Braconidae) is the most used and the most important in Brazil. However, the occurrence of protozoa, microsporidia of the genus Nosema, has been one of the factors that most limit mass production of Diatraea saccharalis in laboratories for the production of Cotesia flavipes in sugarcane biological programs, due to the ease of transmission of this microsporid from generation to generation in the host, the difficulties of control due to the lack of specific antibiotics, and the identification of individuals with a low level of infection, aloows the pathogenic agent to remain endemic in the creation, compromising parasitoid production. The objective of this work was to test the effect of two antibiotics in the control of this protozoan that develops in the diet of D. saccharalis creations. The treatments used were Annita ® (nitazoxonida D1- 500mg + diet; nitazoxonida D2 - 250mg + diet) e Flagyl ® (metronidazol D1- 400mg + diet; metronidazol D2 - 200mg + diet), compared with the Control (standard diet). The results showed that of the antibiotics tested, Annita ® (nitazoxanide) and Flagyl® (metronidazole) at dosages (D1 and D ½), controlled protozoa and provided that they were associated with a rigorous selection of caterpillars, pupae and adults with symptoms of infection. by microsporidia, good indices of production efficiency are obtained.
Antibiotics used in artificial diet to create diatraea saccharalis aiming to control protozoa
Keywords: Saccharum spp; Microsporídeos; Criação artificial; Controle biológico; Microsporidia; Artificial creation; Biological control; CIENCIAS AGRARIAS::AGRONOMIA